The association between the adaptive/maladaptive personality dimensions and emotional regulation - Amiri, Sohrab; Navab, Amir Ghasemi (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2018)
This study investigates the associations between the big five personality dimensions, dark personality traits, and the brief form of the Personality Inventory for DSM-5 with Emotion regulation difficulty dimensions. Data was obtained in a sample of normal population (N = 461). Results showed the associations between neuroticism and openness to experience from the big five personality dimensions and emotion regulation difficulty (p < 0.01). Machiavellianism and psychopathy from dark traits was associated with emotion regulation difficulty (p < 0.01). Negative affectivity, detachment, antagonism, disinhibition, and psychoticism showed positive associations with emotion regulation difficulty (p < 0.01). The results of this study expand the understanding of adaptive/maladaptive personality dimensions and indicate how adaptive and maladaptive personality dimensions could explain emotion regulation difficulty.